Memes and Anti-Memes - Gans, Eric Lawrence (2023)
Memes On May 12, 2023, René Girard was immortalized in a New York Times crossword puzzle as the theoretician of mimetic desire. Specifically, the clue to 28 across, Philosopher Girard who coined "mimetic desire" demanded the entry René. This confirmed the accession of Girard’s most familiar concept to the rank of what we call after...